2018
DOI: 10.1021/acs.inorgchem.8b02170
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding in Amorphous Alkaline Earth Carbonates

Abstract: Amorphous intermediates play a crucial role during the crystallization of alkaline earth carbonates. We synthesized amorphous carbonates of magnesium, calcium, strontium, and barium from methanolic solution. The local environment of water and the strength of hydrogen bonding in these hydrated modifications were probed with Fourier transform IR spectroscopy, H NMR spectroscopy, and heteronuclear correlation experiments. Temperature-dependent spin-lattice (T1) relaxation experiments provided information about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 94 publications
(174 reference statements)
4
16
0
2
Order By: Relevance
“…First, this is evidence that the rigid hydrogen-bearing ions/molecules are homogenously distributed throughout the amorphous calcium carbonate nanoparticles; and a similar conclusion was previously reached by others 68,69 . Second, this also rules out the presence of bicarbonate ions (HCO3 -) given the absence of a distinct upfield signal at short contact time (expected in the range of δ( 13 C) ≈ 155-165 ppm 67,70,71 ).…”
Section: Chemical Structure and Compositionmentioning
confidence: 98%
“…First, this is evidence that the rigid hydrogen-bearing ions/molecules are homogenously distributed throughout the amorphous calcium carbonate nanoparticles; and a similar conclusion was previously reached by others 68,69 . Second, this also rules out the presence of bicarbonate ions (HCO3 -) given the absence of a distinct upfield signal at short contact time (expected in the range of δ( 13 C) ≈ 155-165 ppm 67,70,71 ).…”
Section: Chemical Structure and Compositionmentioning
confidence: 98%
“…Note that no carbonate was detected in the reaction mixture as followed from the absence of the corresponding signals in 13 C NMR spectra (d ¼ 166-168 ppm). 56…”
Section: Kb I Electrolytementioning
confidence: 99%
“…The stabilizing effect has long been thought to originate in the relatively high dehydration energy of Mg 2+ compared to Ca 2+ , arguing that magnesium ions bind water more strongly, thereby reducing mobility of the ions. , However, recent studies have shown that diffusion of water is significantly faster in amorphous magnesium carbonate (AMC) compared to amorphous calcium carbonate (ACC) and even compared to mixed phases (amorphous calcium magnesium carbonate, ACMC) with as much as 73% Mg/(Ca + Mg), suggesting that calcium reduces water mobility more effectively than magnesium, despite the lower dehydration energy. , It has also been shown that magnesium incorporates a much larger portion of hydroxide ions into the amorphous carbonate phase compared to calcium, which provides additional stabilization. ,, …”
Section: Introductionmentioning
confidence: 99%